Marketing Practices in SMEs. Case Study: Romania vs. Malta. (7th June 2016) - Izvercian, Monica; Miclea, Şerban; Potra, Sabina
Abstract: This paper aims to analyse the marketing practices embraced by SMEs managers to fulfil their organisation objectives in terms of profit. Based on a literature review, qualitative interviews and a quantitative research based on questionnaires implemented on Romanian and Maltese SMEs, we have acquired a broad imagine of the marketing practices used within these organisations. The primary pursued objective of the paper is to determine if the size of a SME (in terms of turnover and employee number), influences the marketing process. Moreover, the results of the case study (Romanian vs. Maltese SMEs) outline that SMEs managers, more or less, set short term marketing objectives based on "entrepreneurial instinct" or conjuncture, to overcome threats or to transform opportunities in short term profit. Thus, the study results represent a starting point for developing processes to help SMEs managers make a better use of the marketing orientation concept, in order to create long term business plans.